Empowering and Strengthening Social Care Values Through Orphan Support Activities in Bogor - Ahmad Yani; Ajoe Kartika Mastaka; Iriana WS; Supriyanto (PT. LITERASI SAINS NUSANTARA, 2026)
Community Service (PkM) represents a practical implementation of the Tridharma of Higher Education, which emphasizes the responsibility of universities to contribute to social development and community welfare. One form of community service with significant social and humanitarian impact is the provision of assistance to orphaned children. This community engagement program was organized by Sekolah Tinggi Manajemen LABORA on May 22–23, 2026, in Bogor, involving lecturers and educational staff as active participants. The program aimed to strengthen social awareness among academic members, provide material and emotional support to orphaned children, and foster values of empathy, solidarity, and social responsibility. The implementation process consisted of four stages: planning, fundraising, assistance distribution, and evaluation. The results indicate that the activity contributed positively to the well-being of the beneficiaries, strengthened relationships between the university and the local community, and generated academic outputs in the form of scientific publications. Furthermore, the program provided reflective learning experiences for participants, enabling them to internalize humanitarian values and social responsibility. Therefore, orphan support activities can serve as an effective community service model that integrates social, humanitarian, spiritual, and academic dimensions.